2013
DOI: 10.3109/13625187.2013.813930
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ulipristal acetate on sperm DNA fragmentation duringin vitroincubation

Abstract: During in vitro sperm capacitation DNA fragmentation increased but the latter was counteracted in the presence of UPA, which possibly acted as a scavenger of reactive oxygen species produced by spermatozoa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…Our results show that UPA is capable of interacting with the sperm P-binding sites as judged by the reduction in the percentage of labeled cells observed when UPA is present at concentrations higher than 1000 ng/mL. Our findings provide a convincing explanation for the lack of effect of UPA on different functional parameters evaluated here and in previous works [12,27]. Thus, our observations also indicate that UPA does not interfere with the binding of P to spermatozoa at the concentrations expected to be present in the plasma of EC users.…”
Section: Discussionsupporting
confidence: 80%
“…Our results show that UPA is capable of interacting with the sperm P-binding sites as judged by the reduction in the percentage of labeled cells observed when UPA is present at concentrations higher than 1000 ng/mL. Our findings provide a convincing explanation for the lack of effect of UPA on different functional parameters evaluated here and in previous works [12,27]. Thus, our observations also indicate that UPA does not interfere with the binding of P to spermatozoa at the concentrations expected to be present in the plasma of EC users.…”
Section: Discussionsupporting
confidence: 80%
“…It was previously reported that human spermatozoa exposed in vitro to UPA concentrations similar to those found in the serum of emergency contraceptive pill users (100-200 ng/ml) (Blithe et al, 2003) present no differences in viability, protein tyrosine phosphorylation or spontaneous or follicular fluid-induced acrosome reaction (Munuce et al, 2012). However, a significant decrease in sperm DNA fragmentation was observed in the presence of UPA, probably due to the capacity of this compound to capture oxygen-free radicals (Munuce et al, 2013). Whereas these results do not indicate a direct effect of UPA on sperm function, recent reports have revealed that UPA inhibits ciliary beat and muscular contraction of the human Fallopian tube in vitro (Li et al, 2014), opening the possibility of post-ovulatory effects of UPA on gamete transport, fertilization and/or embryo development.…”
Section: Introductionmentioning
confidence: 85%
“…UPA treatment decreased the luteal regression marker MMP1 levels and increased the luteal regression antagonist marker TIMP2 levels, suggesting that luteal regression was not suppressed and that mature follicles failed to ovulate, resulting in unruptured luteinized cysts. It has been reported that administration of UPA to uterine broids leads to the degradation of hydrogen peroxide and production of reactive oxygen species (ROS) [27], and UPA with sperm possibly acts as a scavenger of ROS [9][28]. In the present study, UPA was administered to normal ovaries, and immunohistological examination revealed that SOD-1 and catalase, which are related to ROS, were decreased by UPA administration in all but primordial follicles.…”
Section: Discussionmentioning
confidence: 46%
“…It has been suggested that UPA could have anti-proliferative functions in uterine broid cells, whereas it may not have severe effects on normal uterine smooth muscle tissue, and UPA treatment generally maintains the endogenous secretion of estrogens [8]. However, long-term use of UPA affects the uterine epithelium, which is known as PR-modulator-associated endometrial change (PAEC) [9]. The pathophysiology of PAEC remains to be elucidated; however, the activation of PR could be attributed to the occurrence of PAEC.…”
Section: Introductionmentioning
confidence: 99%